2014
DOI: 10.1530/jme-13-0187
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic transcription of estrogen receptors in cod gonads throughout a reproductive cycle

Abstract: The role of sex steroid regulation in gonadal maturation is a very complex process that is far from being fully understood. Hence, we have investigated seasonal changes in gonadal expression of estrogen receptors (ERs) in Atlantic cod (Gadus morhua L.), a batch spawner, throughout the annual reproductive cycle. Three nuclear ER partial cDNA sequences (esr1, esr2a, and esr2b) were cloned and all esr transcripts were detected mainly in liver and gonads of fish of both sexes. In situ hybridization of esrs along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 62 publications
4
14
0
Order By: Relevance
“…And higher ESR2 mRNA levels during spring and autumn active periods also might be due to decreases in estrogen levels. However, changes of ESR1 expression levels during reproductive cycle were consistent with the previous studies in cod (Nagasawa et al, 2014) and Italian wall lizard (Verderame and Limatola, 2010), of which the highest expression of ESR1…”
Section: Accepted Manuscriptsupporting
confidence: 91%
See 2 more Smart Citations
“…And higher ESR2 mRNA levels during spring and autumn active periods also might be due to decreases in estrogen levels. However, changes of ESR1 expression levels during reproductive cycle were consistent with the previous studies in cod (Nagasawa et al, 2014) and Italian wall lizard (Verderame and Limatola, 2010), of which the highest expression of ESR1…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…However, in female alligators, the mRNA expression level of ESR1 was higher than that of ESR2 in the hypothalamus and liver, which was consistent with the previous reports in the cod (Nagasawa et al, 2014), Italian wall lizard (Verderame and Limatola, 2010), leopard gecko (Endo et al, 2008) and bovine (Panin et al, 2015).…”
Section: Accepted Manuscriptsupporting
confidence: 91%
See 1 more Smart Citation
“…It has been reported that testosterone levels changed in parallel with spermatogenic activity in the testis. A very recent study suggests that expression of esr genes help in growth and differentiation for Leydig cell in testis throughout the annual reproductive cycle in Atlantic cod (Nagasawa et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the interstices between the convoluting seminiferous tubules are packed with areolar connective containing blood capillaries, lymph vessels and interstitial Leydig cells, which secrete testosterone in the breeding season. A very recent study suggests that expression of esr genes help in growth and differentiation for Leydig cell in testis throughout the annual reproductive cycle in Atlantic cod (Nagasawa et al 2014). On the contrary, interstitial tissue of the regressed testes of the nonbreeding season appears more prominent (Loft and Murton, 1973).…”
Section: Introductionmentioning
confidence: 99%